Effect of Inflation, Rupiah Exchange, Dow Jones Index, Nasdaq Index, and S & P500 Index Against Combined Stock Price Index - Abdul Manap; Sugito Sugito; Yusnindar Yusnindar; Atik Sekianti (West Science Interdisciplinary Studies, 2024)
This research aims to determine empirical evidence of the influence of inflation, Rupiah exchange rate, Dow Jones index, Nasdaq index, A & P500 index on the Composite Stock Price Index. The research uses quantitative methods and uses classical assumption tests, multiple regression analysis, and hypothesis testing. The data used is secondary data during the period January 2019 – November 2023, resulting in a total of 59 samples from each variable using the purposive sampling method. The research results show that inflation has an effect on the Composite Stock Price Index, the Rupiah exchange rate has no effect on the Composite Stock Price Index, the Dow Jones Index has an effect on the Stock Price Index Combined, the Nasdaq Index influences the Composite Stock Price Index, the S & P500 Index influences the Composite Stock Price Index, and Inflation, the Rupiah Exchange Rate, the Dow Jones Index, the Nasdaq Index, and the S & P500 Index simultaneously influence the Composite Stock Price Index.